Colecistectomia laparoscópica com 02 portais e anzóis acessórios: padronização técnica e avaliação dos resultados em 415 pacientes consecutivos - Batista, Gustavo Adolfo Pavan (2016)
Introduction: Cholecystectomy is one of the most performed abdominal surgical procedures in Brazil and worldwide. Its surgical technique development benefited most from the advent of laparoscopy. The laparoscopic cholecystectomy with two ports and traction hooks was idealized as a less invasive, low cost alternative to the golden standard. This study intends to determine the safety and feasibility of the procedure and also establish its technical standardization. Methods: The proposed technique (two trocar portals with the addition of two traction hooks) was performed to 415 patients over the course of 6 years. All subjects were operated by the same surgeon, in the same institution. Results: Surgical mean time was 49 minutes, with the majority of the procedures (79.76%) under the 60 minutes time frame. The conversion rate for conventional laparoscopy or laparotomy was 2.10%; if the adding of extra traction devices were considered, 4.10%. In those cases, there was a significant correlation between the complexity of the procedure and the conversion rate (p = 0.026), xvii xvii considering acute cholecystitis, exploration of biliary tract and concomitant procedures as criteria for higher complexity. The length of hospital stay was characterized by predominance of discharge on the next day after surgery (93,73%), also related to the procedures complexity (p < 0.001). These results were comparable to the medical literature regarding the gold standard procedure. Conclusion: Laparoscopic cholecystectomy with two ports and accessory traction hook-shaped devices is a safe procedure and can be offered as a therapeutic option to patients with a clinical indication for cholecystectomy.